Pesticide removal by fluvial biofilms in lowland streams under different land uses and agricultural seasons - M. A. Mujica; E. De Gerónimo; A. Mosca; S. L. Fanelli; A. H. Paracampo; J. Cochero (International Journal of Environmental Science and Technology, 2026)

The teat skin microbiota of organic primiparous dairy cows is dynamic during the transition period - C.J. Dean; T. Ray; F. Peña-Mosca; T.J. Wehri; K. Sharpe; A.M. Antunes; E. Doster; L. Fernandes; V.F. Calles; C. Bauman; B. Heins; P. Pinedo; et al. (Preventive Veterinary Medicine, 2025)

Quantitative detection of Colletotrichum godetiae and C. acutatum sensu stricto in the phyllosphere and carposphere of olive during four phenological phases - Leonardo Schena; Ahmed Abdelfattah; Saveria Mosca; Maria G. Li Destri Nicosia; Giovanni E. Agosteo; Santa O. Cacciola (European Journal of Plant Pathology, 2017)

The Monviso Massif and the Cottian Alps as Symbols of the Alpine Chain and Geological Heritage in Piemonte, Italy - Franco Rolfo; Piera Benna; Paola Cadoppi; Daniele Castelli; Sergio E. Favero-Longo; Marco Giardino; Gianni Balestro; Elena Belluso; Alessandro Borghi; Fernando Cámara; Roberto Compagnoni; Simona Ferrando; et al. (Geoheritage, 2015)

Evaluation of the measurement uncertainty in automated long-term sampling of PCDD/PCDFs - M. Vicaretti; G. D’Emilia; S. Mosca; E. Guerriero; M. Rotatori (Environmental Science and Pollution Research, 2013)

The geographical and environmental determinants of genetic diversity for four alpine conifers of the E uropean A lps - E. Mosca; A. J. Eckert; E. A. Di Pierro; D. Rocchini; Nicola La Porta; P. Belletti; D. B. Neale (Molecular Ecology, 2012)
Climate is one of the most important drivers of local adaptation in forest tree species. Standing levels of genetic diversity and structure within and among natural populations of forest trees are determined by the interplay between climatic heterogeneity and the balance between selection and gene flow. To investigate this interplay, single nucleotide polymorphisms ( SNP s) were genotyped in 24 to 37 populations from four subalpine conifers, Abies alba Mill., Larix decidua Mill., Pinus cembra L. and Pinus mugo Turra, across their natural ranges in the Italian Alps and Apennines. Patterns of population structure were apparent using a Bayesian clustering program, STRUCTURE , which identified three to five genetic groups per species. Geographical correlates with these patterns, however, were only apparent for P. cembra . Multivariate environmental variables [i.e. principal components (PCs)] were subsequently tested for association with SNP s using a Bayesian generalized linear mixed model. The majority of the SNP s, ranging from six in L. decidu a to 18 in P. mugo , were associated with PC 1, corresponding to winter precipitation and seasonal minimum temperature. In A. alba , four SNP s were associated with PC 2, corresponding to the seasonal minimum temperature. Functional annotation of those genes with the orthologs in Arabidopsis revealed several genes involved in abiotic stress response. This study provides a detailed assessment of population structure and its association with environment and geography in four coniferous species in the Italian mountains.

Long-term automated sampling of PCDD/PCDF flue gas: current status and critical issues - M. Vicaretti; S. Mosca; E. Guerriero; M. Rotatori (Environmental Science and Pollution Research, 2012)

Concentration of organic micropollutants in the atmosphere of Trieste, Italy - S. Mosca; G. N. Torelli; G. Tramontana; E. Guerriero; M. Rotatori; M. Bianchini (Environmental Science and Pollution Research, 2012)

In vivo key role of reactive oxygen species and NHE-1 activation in determining excessive cardiac hypertrophy - Oscar H. Cingolani; Néstor G. Pérez; Irene L. Ennis; María C. Álvarez; Susana M. Mosca; Guillermo R. Schinella; Eduardo M. Escudero; Gloria Cónsole; Horacio E. Cingolani (Pflügers Archiv - European Journal of Physiology, 2011)

Lack of feral livestock interference with native guanaco during the dry season in a South American desert - Ramiro J. A. Ovejero; Pablo Acebes; Juan E. Malo; Juan Traba; Maria Eugenia Mosca Torres; Carlos E. Borghi (European Journal of Wildlife Research, 2011)

Comparison of the protective effects of ischemic preconditioning and the Na + /H + exchanger blockade - Susana M. Mosca; Horacio E. Cingolani (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Is stunning prevented by ischemic preconditioning? - Susana M. Mosca; Ricardo J. Gelpi; Jose Milei; Graciela Fernández Alonso; Horacio E. Cingolani (Molecular and Cellular Biochemistry, 1998)